The effect of Maleic Anhydride Grafted Polypropylene on Thermo-Oxidative ageing of paper sludge filled Polypropylene/Ethylene Propylene Diene terpolymer composites - Ibrahim, Ismail; Salmah, Husseinsyah; Nor Azwin, Ahad (Universiti Kuala Lumpur (UniKL), 2010)
Organized by Universiti Kuala Lumpur (UniKL), 27th - 28th November 2007 at Kuala Lumpur, Malaysia.